Identification of Extreme Risk Factors for Construction Time and Cost Performance in Surabaya Housing - joshua wijaya; Paulus Nugraha; Jani Rahardjo (Dimensi Utama Teknik Sipil, 2020)
The importance level of risk throughout the construction progress is apparently inherit tendermous impact on the ultimate project performance and client satisfaction. Such determination level of risk in terms of frequency, time risk as well as cost effect to be perceived from two perspectives, owner and contractor, is inventably crucial to be researched, primarily for housing construction in Surabaya. This study was conducted by applying a survey through some questionnaires to observe 30 risks that have been identified from the previous literature. Total respondents involved were 69 respondents consisting of 29 respondents representing the owner / developer and 40 respondents representing the contractor. The results of this research, as from owners’ perspective, shows bad weather was the most common risk, followed by contractors’ financial difficulties which has the utmost impact on time and increasing material price takes major part on costs respectively. Whereas according to the contractor, design changes from consultants / owners are the most frequent risks, design changes from consultants / owners have prominent impact on time and lastly worker productivity also siginificantly reinforces expense factor.